Extending asphalt pavement life with thin whitetopping - Sultana, Sharmin (Kansas State University, 2010)
Due to budget constraints, many highway agencies are becoming interested in pavement preservation or rehabilitation rather than reconstruction to ensure pavement is in serviceable condition. Thin whitetopping (TWT) is the process of rehabilitation of distressed asphalt concrete (AC) pavements using a concrete overlay. This study was done to develop a design catalog for existing AC pavements to be overlaid with TWT. The finite element (FE) analysis was performed with SolidWorks, a 3-D FE software program to develop this design catalog. The design considered different TWT thicknesses, existing AC layer thicknesses and modulus, bonding conditions between TWT and existing AC layer, shoulder conditions and temperature differentials. Each model was built as a three-layer pavement system—concrete (TWT), asphalt layer, and subgrade soil. The traffic load was modeled as a constant pressure with a rectangular area applied at the surface and with intensity equal to the tire inflation pressure of 100 psi. The expected lives of TWT overlays were estimated using fatigue equations developed by the Portland Cement Association (PCA). Results obtained from this study show that interface bonding condition is the most important factor affecting the behavior of TWT. With the increase of TWT thickness or existing AC thickness or AC modulus, and addition of paved shoulder, concrete tensile stress decreases. Curling stress increases with the increase of TWT thickness and is not a function of AC properties. A design catalog was developed in terms of service life of the pavement. Unlike unbonded TWT with unpaved shoulder that results in catastrophic loss of rehabilitated pavement life, bonded TWT is expected to last 10 years, assumed in design. Thus, proper bonding must be ensured in order to have extended pavement life.
Keywords: Thin whitetopping; Engineering, Civil (0543)